Documentary Films As An Educational Medium On The Gaming World And Teenagers' Emotions - I Putu Huwa Bagus Utama; I Wayan Suardana; I Nengah Wirakesuma (UNIVERSITAS PAKUAN, 2026)
This study aims to produce a documentary film as an educational medium to explore the impact of gaming on adolescents’ emotional development. The research applies a practice-based approach using both qualitative and quantitative methods. Data were collected through in-depth interviews, participatory observation, and questionnaires involving adolescents, parents, and experts. The findings indicate that most adolescents engage in gaming daily with durations exceeding three hours. This activity generates various emotional responses, including enjoyment, satisfaction, frustration, and anger. Gaming provides positive impacts such as entertainment, cognitive skill development, and social interaction, but also presents negative effects, including addiction, emotional instability, and reduced direct social engagement. The documentary film is designed using an expository approach to present balanced and reflective perspectives. The results suggest that documentary film is an effective educational medium to raise awareness among adolescents and parents regarding balanced game use in daily life